Healthy Eating Behavior Patterns of Department of Health Personnel - Chamnankong, Kingpikul; Kiatadisorn, Rumpai (Journal of Preventive Medicine Association of Thailand, 2021)
This study applied cross sectional descriptive study to study eating habits for health among health personnel of the Department of Health (DoH), Ministry of Public Health, and explore factors and their relationships with eating habits for health and Quantitative data were collected from 260 DoH workers. Interviews were conducted among executives, technical health workers, and workers in the support sector. The quantitative data analysis showed that 55.0 percent and 31.9 percent of the participants were aware of their eating behaviors that it should be healthy and 13.1 percent reported that they should be stricter with their eating habits. The leading factor for health status were body mass index, supplementary factor for family members eating together, a friend invites you for tea or sweetened coffee, a friend bought some sweets for me, a friend recommends healthy eating. There was a statistically significant correlation with food consumption behavior patterns among health personnel under the DoH (p.< 0.05) DoH should promote healthy eating habits among its personnel by supporting them to carry out group activities in which friends encourage friends to have healthy food and enforcing strict policies that food and drink shops reduce sugar, fat, and salt contents in their products.